Highly sliding-wear resistant B4C composites fabricated by spark-plasma sintering with Ti–Al additives. (1st March 2020) - Ortiz, Angel L.; Galán, Carlos A.; Borrero-López, Oscar; Guiberteau, Fernando
Abstract: The lubricated sliding-wear resistance of a fine-grained B4 C composite fabricated by transient liquid-phase assisted spark-plasma sintering with Ti–Al additives at smooth conditions is critically compared to that of its reference monolithic B4 C ceramic. It is shown that the former has an excellent sliding-wear resistance that exceeds that of the later by one order of magnitude (far less specific wear rate, worn volume, and wear damage), attributable to its greater hardness and densification. The wear mode is abrasion dominated by plastic deformation, plus localized microfracture in the monolithic ceramic. Implications for fabricating highly wear-resistant tribocomponents based on superhard ceramics are presented. Graphical abstract: Image, graphical abstract